ANALISIS PENGARUH KUALITAS PELAYANAN ONLINE RESERVATION TICKET TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada PT Kereta Api Indonesia Daop 4 Semarang) - Muhammad Ariefian Isnan; Sutopo Sutopo (JURNAL STUDI MANAJEMEN ORGANISASI, 2017)
The background of this research is the accumulation of passengers at ticket counter atdeparture station that indicates a lack of interest in using online reservation ticketservice. This research aims to analyze and provide empirical evidence about the influenceof the four variables of quality electronic services are efficiency (X1), fulfillment (X2),system availability (X3), dan privacy (X4) to customer satisfaction users onlinereservation ticket of PT Kereta Api Indonesia Daop 4 Semarang.Data analysis techniques used in this research is multiple regression analysis. Thepopulation in this study was the passengers that uses the online reservation ticket in thePT Kereta Api Indonesia Daop 4 Semarang. The amount of sampels are 100 respondensand the sampling method is purposive sampling. The data was collected usingquestionnaires.The t test result show that only variables efficiency, fulfillment, and system availabilityhave a positive and significant effect on customer satisfaction .while privacy variable notpositive and significant effect on customer satisfaction. The multiple linier regressionresult show that efficiency variable are independent variables that most influence on thecustomer satisfaction.Keywords: quality of service, efficiency, fulfillment, system availability, privacy, customersatisfaction